2000
DOI: 10.3184/030823400103167859
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Proton Transfer from the Hydroxy O Atom to the Imine N Atom, Crystal structure of N-Salicylideneamine-1-Tris(Hydroxymethyl)Methane

Abstract: The structural study of the Schiff base compound, N-salicylideneamine-1-tris(hydroxymethyl)-methane, confirmed that the hydroxy H atom has transferred to the imine N atom with the intramolecular O…N bond being 2.6215(19) Å. Fig. 1 X-ray crystal structure of N-salicylideneamine-1tris(hydroxymethyl)-methane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2003
2003
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…A mixture of aniline (0.93 g, 10 mmol), water (50 mL) and concentrated hydrochloride acid (2.5 mL, 30 mmol) was 15 …”
Section: Synthesismentioning
confidence: 99%
“…A mixture of aniline (0.93 g, 10 mmol), water (50 mL) and concentrated hydrochloride acid (2.5 mL, 30 mmol) was 15 …”
Section: Synthesismentioning
confidence: 99%
“…For instance, Chumakov et al [33] found that at 292 K the unit cell of compound 14 contains two tautomeric molecules with imine and enamine forms, respectively. However, Cungen et al [34] could only locate the enamine form at 298 K, a result further corroborated by Büyükgüngör and co-workers [35] at 208 K. The structures of a series of Schiff bases generated from TRIS and salicylaldehydes bearing different substituents -5-nitro- (15) [36] and 3-hydroxy-(16) at 223 K, [35] 3-methoxy-(17) at 213 K, [35] and 5-phenylazo-(18) [37] -were all determined to be enamine tautomers in the solid state. In the cases of the halogenated derivatives 19 [33] and 20, [36] the unit cell contains two molecules at 293 K, although both exhibit an enamine structure.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of compounds 1-3 was based on previous articles; nevertheless, variations in the reaction conditions were necessary. [21][22][23][24] The ei/ka tautomeric equilibrium of aromatic Schiff bases can be observed via UV-Vis, IR and NMR spectroscopy. UV-Vis spectra of 1-3 showed the tautomers' transitions that were assigned with the help of TDDFT simulations.…”
Section: Synthesis Of 1-3mentioning
confidence: 99%